The Effect of Banana Leaf as Poultice on Wound Healing In Rabbits - Al-Mutheffer, E’atelaf A. (The Iraqi Journal of Veterinary Medicine, 2013)
The objective of this study is to determine the effectiveness of banana leafs as a wound dressing in rabbits. Ten adults local breed male rabbits weighing between 1.5 – 2 kg were used. The animals were divided into two equal groups. Animals were anesthetized by xylazine 5 mg / kg BW mixed with ketamine 40 mg / kg BW intramuscularly. Under aseptic technique (4-6) avulsion wounds 1cm in diameter were made on the back region of each rabbit. Control group didn’t receive any treatment, while the treated group the wounds were covered by the banana leaf as poultice for 14 days. Histopathological and gross evaluation revealed that there are significant differences between the two groups, because banana leaf provides a clean, waxy non adherent, water proof, and cheap dress to prevent the wound from the contaminated external environment